2021
DOI: 10.3390/pathogens10060680
|View full text |Cite
|
Sign up to set email alerts
|

A Virus-Like Particle-Based Vaccine Candidate against the Tick-Borne Powassan Virus Induces Neutralizing Antibodies in a Mouse Model

Abstract: Powassan virus (POWV) is a tick-borne flavivirus circulating in North America and the Russian Far East that can cause severe neuroinvasive diseases, including encephalitis, meningitis, and meningoencephalitis. The reported neuroinvasive case fatality is about 10%, and approximately 50% of the survivors from the neuroinfection exhibit long-lasting or permanent neurological sequelae. Currently, treatment of POWV infection is supportive, and no FDA-approved vaccines or specific therapeutics are available. A novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Interestingly, the POWV 351–359 region containing a CD8 + T cell epitope also contains an POWV-specific B cell epitope identified by Choi et al (2020) in their synthetic enhanced DNA-based POWV vaccination approach ( Choi et al, 2020 ). These concomitant findings, as well as other studies ( Cimica et al, 2021 ), underscore the benefit of a VLP-based vaccination strategy that elicits responses to B and T cell epitopes. This finding also highlights the need to better understand immune responses elicited by different vaccine formulations (i.e., different adjuvants driving T-helper profiles, T H 1 versus T H 2) to provide optimal immunity against POWV-LB.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, the POWV 351–359 region containing a CD8 + T cell epitope also contains an POWV-specific B cell epitope identified by Choi et al (2020) in their synthetic enhanced DNA-based POWV vaccination approach ( Choi et al, 2020 ). These concomitant findings, as well as other studies ( Cimica et al, 2021 ), underscore the benefit of a VLP-based vaccination strategy that elicits responses to B and T cell epitopes. This finding also highlights the need to better understand immune responses elicited by different vaccine formulations (i.e., different adjuvants driving T-helper profiles, T H 1 versus T H 2) to provide optimal immunity against POWV-LB.…”
Section: Discussionsupporting
confidence: 74%
“…Both a lipid nanoparticle (LNP)-encapsulated modified mRNA vaccine and a synthetic DNA vaccine encoding the POWV prM and E genes elicited potently neutralizing antibodies in serum and conferred protection in lethal challenge models in mice [ 29 , 30 ]. Another study demonstrated that a POWV virus-like particle (VLP), which also included the POWV prM and E genes, elicited strong neutralizing antibody responses [ 31 ]. Our immunogen, based solely on the recombinant EDIII-subunit, elicited potently neutralizing and protective antibodies in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work toward POWV vaccine development, which includes the investigation of mRNA [ 29 ], DNA [ 30 ] and VLP [ 31 ] platforms, has focused on the presentation of POWV prM and E proteins as the antigen. While these platforms have demonstrated the induction of neutralizing and protective antibody responses in mice, the full prM and E proteins contain many antigenic sites, only a subset of which are targets of functional antibodies that limit POWV infection.…”
Section: Introductionmentioning
confidence: 99%
“…These are summarized in Table 3. In general, nucleic acid-based (mRNA: [70] DNA: [70]), virus-like particle-based [77,172], and nanoparticle-based [69] vaccination strategies have been shown to be efficacious in murine models. Monoclonal antibodies elicited by vaccination have been demonstrated to be important for protection against POWV infection [63,70,173].…”
Section: Powvmentioning
confidence: 99%